2016
DOI: 10.22161/ijeab/1.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vermicompost on Yield and Yield Components of Two Corn Cultivars

Abstract: Abstract-This study was performed for evaluation of vermicompost Effect on yield and yield components of two corn cultivars. First factor included cultivars (S.C 704, B.C 666) and second factor included vermicompost treatments (control, 25, 50, 75 and 100%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The lowest result (15.70 cm) was recorded in S2 nutrient level treatment which was statistically significant with S5 treatment with the value of 16.15 cm (Table 1). Our results suggested that an adequate supply of nutrients from both organic and inorganic sources throughout vegetative growth was necessary for proper cob development in maize, as also reported by Samsami (2016). In the case of S2, the cob may be devoid of recommended demand of nutrients resulted in the lowest cob length.…”
Section: Yield and Yield Attributes Cob Lengthsupporting
confidence: 84%
“…The lowest result (15.70 cm) was recorded in S2 nutrient level treatment which was statistically significant with S5 treatment with the value of 16.15 cm (Table 1). Our results suggested that an adequate supply of nutrients from both organic and inorganic sources throughout vegetative growth was necessary for proper cob development in maize, as also reported by Samsami (2016). In the case of S2, the cob may be devoid of recommended demand of nutrients resulted in the lowest cob length.…”
Section: Yield and Yield Attributes Cob Lengthsupporting
confidence: 84%